Enfermedad periodontal asociada a sindrome de inmunodeficiencia adquirida SIDA - Soto, Jorge Enrique (Revista Estomatología, 1993)
In the early 80’s an infectious disease appears creating serious problems in die delivery of heal the careo The viral agent belongs to the retrovirus family: Human inmunodeficient vims which causes the adquired inmunodeficienty syndrollle (AIOS); it was isolated between 1982 1984. The genetic material of retrovirus is RNA, and he has die transcriptasa that uses the vibrio RNA to produce ONA. HIV infects T 4 c.-ells amI cells that llave C4 complex celular cleadl is produced through severru mechanislll mnong whieh we have apoptosis. Patients with severe inmunosuppression as consequence of infection by HIV are at risk for a number of severe disease caused by opportunistic agents. Oral involvement is one of the first signs of the disease, this indudes periodontal clisease seen in HIV infected persons (HIV -P), HIV associated gingivitis ancl necrotizing stomatilis of periodontal origino. Treatrnent of these lesions re(!llires debridement local, antimicrobial therapy amI imecliate follow-up care.